Kajian Sense of Place sebelum dilakukan Revitalisasi pada Kawasan Kota Tua Cimanuk Indramayu - Muhammad Luthfi Almakhi; Ira Darwin (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. The Cimanuk Old Town Area has a long history from pre-colonial times to the present, especially with regard to the Cimanuk Port which functions as a distribution center for agricultural products. In the pre-colonial period, Cimanuk Port was used as a magnet for economic activity and became the choice of residence for immigrants. During the Dutch colonial period, the construction of the Pos Highway and diverting distribution from the waterway to the land route made the prestige of Cimanuk Harbor and the surrounding urban areas dim and experience a decline in function in the present. This is the basis of this research with the aim of exploring the meaning of a place (sense of peace) in The Cimanuk Old Town Area so that historical documents are recorded in its development, especially when a discourse is being rolled out to revitalize the area. This study uses a combination method (mix methods). In the first stage, the research used descriptive qualitative analysis method in identifying the sense of place through the description of the physical form of the area and the description of human activities in it by first dividing the blocks in the area based on the results of observations and interviews. For the second stage, using the Rasch models analysis method in identifying the level of sense of place, through distributing questionnaires based on people's perceptions. This study explains that the results for the first stage show that the Cimanuk Old Town Area tends to be linear, following the pattern of the road network and the Cimanuk River flow and has a diversity of activities in the Cimanuk Old Town Area. For the second stage, the results show a low level of sense of place attachement, place attachment, place identity and community dependence in activities in The Cimanuk Old Town area. Abstrak. Kawasan Kota Tua Cimanuk memiliki sejarah yang panjang dari masa prakolonial hingga saat ini terutama yang berkaitan dengan Pelabuhan Cimanuk yang berfungsi sebagai pusat distribusi hasil pertanian. Pada masa prakolonial, Pelabuhan Cimanuk dijadikan magnet kegiatan perekonomian dan menjadi pilihan bermukim para pendatang. Pada masa kolonial Belanda adanya pembangunan Jalan Raya Pos dan mengalihkan distribusi dari jalur air menuju jalur darat menjadikan pamor Pelabuhan Cimanuk dan kawasan perkotaan disekitarnya meredup dan mengalami penurunan fungsi di masa sekarang. Hal tersebut menjadi dasar dari penelitian ini dengan tujuan untuk mengekspIorasi makna suatu tempat (sense of pIace) pada Kawasan Kota Tua Cimanuk agar tercatatnya dokumen sejarah dalam perkembangannya, terlebih saat ini digulirkan wacana untuk merevitalisasi kawasan tersebut. Penelitian ini menggunakan metode kombinasi (mix metods). Pada tahap pertama, penelitian menggunakan metode analisis kualitatif deskriptif dalam mengidentifikasi gambaran sense of place melalui gambaran bentuk fisik kawasan dan gambaran aktivitas manusia di dalamnya dengan terlebih dahulu membagi blok pada kawasan berdasarkan hasil observasi dan wawancara. Untuk tahap kedua, mengggunakan metode analisis rasch models dalam mengidentifikasi tingkat sense of place, melalui penyebaran kuesioner berdasarkan persepsi masyarakat. Penelitian ini menjelaskan bahwa hasil untuk tahap pertama, menunjukkan Kawasan Kota Tua Cimanuk cenderung berbentuk linier yang mengikuti pola jaringan jalan dan aliran Sungai Cimanuk serta memiliki keragaman aktivitas di Kawasan Kota Tua Cimanuk. Untuk tahap yang kedua, hasilnya menunjukkan tingkat sense of place rendah yang dibentuk oleh keterikatan tempat, identitas tempat dan ketergantungan masyarakat dalam berkegiatan di Kawasan Kota Tua Cimanuk.